Effects of positive social comparative feedback on motor sequence learning and performance expectancies - Lewis, Allison F.; Bohnenkamp, Rachel; Johnson, Lynn; den Ouden, Dirk B.; Wilcox, Sara; Fritz, Stacy L.; Stewart, Jill Campbell (Frontiers in Psychology, 2023)
Positive social comparative feedback indicates to the learner that they are performing better than others. While this type feedback supports motor skill learning in some tasks, the effect of social comparative feedback on implicit motor sequence learning remains unknown. The aim of this study was to determine the effect of positive social comparative feedback on the learning of and expectancies for a motor sequence task. Forty-eight individuals practiced a joystick-based sequence task and were divided into three feedback groups: CONTROL (no performance feedback), RT ONLY (response time only feedback), and RT+POS (response time plus positive social comparison). Participants attended sessions on two consecutive days: Day 1 for repetitive motor practice/skill acquisition and Day 2 for retention testing. Performance related expectancies, like perceived competence, were measured before and after motor practice on Day 1 and at retention on Day 2. While all groups improved with practice, the CONTROL group showed better overall performance/learning (faster response times) compared with the RT ONLY group. Despite similar response times, the RT+POS showed higher peak velocities than the RT ONLY group. Overall, the RT+POS and CONTROL demonstrated increases in perceived competence while the RT ONLY group did not. The results of this study suggest that feedback content is an important consideration during motor practice sessions since feedback without context (RT ONLY) may be detrimental to motor sequence learning. The results also suggest that, if providing performance related feedback during practice of a skill that relies on implicit sequence learning processes, comparative context may be necessary for enhancing expectancies and supporting learning.